2007
DOI: 10.1093/rpd/ncm429
|View full text |Cite
|
Sign up to set email alerts
|

Determination of natural radioactivity in drinking water in private dug wells in Akure, Southwestern Nigeria

Abstract: Gamma spectrometry of well water was done to measure the activity concentrations of gamma-emitters 226Ra and 228Ra from 238U and 232Th series, respectively, and 40K in their waters. Measurements were done using high-purity (HPGe) co-axial detectors (Canberra, GC 2018-7500 ) coupled to Canberra Multichannel Analyser system. Activity concentrations ranged from 0.57 to 26.86, 0.20 to 60.06 and 0.35 to 29.01 Bq l(-1) for 226Ra, 228Ra and 40K, respectively. Activity concentrations were compared with data from other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 7 publications
3
10
1
Order By: Relevance
“…Th average value (0.16 Bq•L −1 ) is almost matched with Saudi Arabia (Alseroury et al, 2018), higher than Jordan (Al-Shboul et al, 2017) and lower than other countries. The present results show that the average of 40 K concentration is nearly matching the value of Nigeria (Ajayi & Owolabi, 2007), higher than Yemen (Abdurabu et al, 2016) and Jordan (Al-Shboul et al, 2017), while it is lower than the other observed values. Therefore, we can indicate that the obtained results are in agreement with the data obtained from various locations in the world, taking into account the data of the countries of different geographical locations differ regarding specific mineral.…”
Section: Lifetime Risk Assessment (R)supporting
confidence: 67%
“…Th average value (0.16 Bq•L −1 ) is almost matched with Saudi Arabia (Alseroury et al, 2018), higher than Jordan (Al-Shboul et al, 2017) and lower than other countries. The present results show that the average of 40 K concentration is nearly matching the value of Nigeria (Ajayi & Owolabi, 2007), higher than Yemen (Abdurabu et al, 2016) and Jordan (Al-Shboul et al, 2017), while it is lower than the other observed values. Therefore, we can indicate that the obtained results are in agreement with the data obtained from various locations in the world, taking into account the data of the countries of different geographical locations differ regarding specific mineral.…”
Section: Lifetime Risk Assessment (R)supporting
confidence: 67%
“…Elevated concentrations of 226 Ra (up to 19.6 Bq L − 1 ) in the waters of Saratoga Springs, New York, USA, are linked to an abundance of uranium-bearing minerals associated with granites and metamorphic rocks (Kitto et al, 2005). The 226 Ra activity concentrations up to 27 Bq L − 1 were reported for the dug well waters in southwestern Nigeria which have been attributed to the presence of radioactive minerals such as zircon, allanite, apatite and monazite in the rocks of this area (Ajayi and Owolabi, 2008). The presence of high heat flow in the area surrounding thermal aquifers leads to high water temperatures that enhance the dissolution of radioactive minerals including radium minerals (Roba et al, 2010).…”
Section: Resultsmentioning
confidence: 94%
“…The gamma-ray lines of 352 keV from 214 Pb and 609 keV from 214 Bi were used to evaluate the 226 Ra activity concentration (Canet and Jacquemin 1990;Amrani 2002;Ajayi and Owolabi 2008), while 583 keV gamma-rays from 208 TI and 911 keV from 228 Ac were used to determine to the 232 Th activity concentrations. The activity concentrations of 40 K and 137 Cs were determined by using their 1,460 and 661 keV gamma-ray lines, respectively.…”
Section: Determination Of Radionuclide Concentrationsmentioning
confidence: 99%